2016
DOI: 10.1002/sia.6179
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of positron backscattering on Al, Cu, Ag and Au targets using GEANT4 code

Abstract: In this paper, backscattering of 3 to 50‐keV positrons on Al, Cu, Ag and Au metallic targets has been systematically investigated using GEANT4 code. The dependence of positron backscattering coefficients on atomic number Z, target thickness, incident energy and angles has been discussed comprehensively. Besides, positron backscattering spectra for those metallic targets at different discrete scattering angles were also studied to provide theoretical basis of the most appropriate scattering angle selected for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Figure 8 shows the simulated energy of backscattered positrons for different incident positron energies. In comparison with the results of [27], our simulation in this study indicated that the incident positron energy more strongly influences E m than the material type [27]. Further, for the same material, positrons with lower incident energies present lower E m and better energy resolution.…”
Section: Backscatteringmentioning
confidence: 49%
See 1 more Smart Citation
“…Figure 8 shows the simulated energy of backscattered positrons for different incident positron energies. In comparison with the results of [27], our simulation in this study indicated that the incident positron energy more strongly influences E m than the material type [27]. Further, for the same material, positrons with lower incident energies present lower E m and better energy resolution.…”
Section: Backscatteringmentioning
confidence: 49%
“…The determination of backscattered positrons is important to describe the positron scattering mechanism on the surface of the material, which can then be used to interpret the positron distribution on the surface [26,27]. In our previous work [27], we conducted a comprehensive investigation of positron backscattering coefficients and the backscattering energy as a function of the incident energy, target thickness, incident angles, and atomic number Z. Our results showed that there exists a certain energy (E m ) with a maximal probability of the distribution of backscattered positron energy.…”
Section: Backscatteringmentioning
confidence: 99%
“…The use of GEANT4 for the determination of positron implantation profiles has been validated extensively in the literature through comparison with experimental results. [3][4][5][6][27][28][29][30] As the radioisotope 22 Na is most commonly used in PAS techniques due to its uniquely well-suited decay characteristics of lifetime and coincident decay gamma emission, the β þ spectrum for this decay is used for all simulations. 4,31 This spectrum has no precise analytical form; therefore, the parameterized spectrum is taken from ICRP Publication 107 (nuclear decay data for dosimetric calculations) and is plotted in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The targets considered in this article are solid Al, Cu, Li, Na. For Al and Cu, a number of previous works were available to compare our findings with [15][16][17][18][19][20][21][22][23][24]. Since the transport cross section, range of penetration and number of wide-angle collisions form the basic input for the backscattering calculation, we compare these parameters for both electron and positron scattering to available data [15-17, 22, 25].…”
Section: Introductionmentioning
confidence: 94%
“…In general, the two reported data are not in good agreement with each other. The coefficients reported by Chaoui [22], Bentaben [18] and Lai [23] is computed using Monte Carlo simulation techniques. For Cu, present data is in good agreement with the values reported by Chaoui et al [22].…”
Section: Backscattering Coefficientmentioning
confidence: 99%